THE STUDENTS’ ATTITUDE IN EFL CLASSROOM AT MUHAMMADIYAH UNIVERSITY OF MAKASSAR - Rajab, Abd.; Rahman, A. Qashas; Dollah, Syarifuddin (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2015)
Successful learners are enthusiastic, exhibit confident attitudes toward learning have positive expectations from it and do not experience anxiety about learning. Because the attitude toward learning one has inevitably in fluency the outcomes, the more positive attitudes one has, the better he or she performs in learning. The objectives of this research was to find out the students’ attitude toward lecturer’s explanation at Muhammadiyah University of Makassar. This research employed descriptive Quantitative. The participants of this research were 38 students in F class and 2 Lecturers at Muhammadiyah University of Makassar. The result of the research was collected through the use of Questionnaires and audio-video camera, and then it was calculated and transcribed to be analyzed. The result of research from the questionnaire that was distributed to the 38 students consists of 20 items and open ended question show The Students’ attitudes toward lectures explanation at Muhammadiyah University of Makassar were good attitude (82).It was the students’ students’ attitude toward lecturer’s explanation in EFL classroom at University Muhammadiyah of Makassar is positive. The Students have positive attitude toward lecturer in presenting the material in the classroom. Besides that, they perceive that teacher’s explanation that showed by the lecturer are prepare, enthusiasm, summarizing, good explanation, sympathy, friendly. Good characteristics of lecturers’ explanation in EFL classroom at University Muhammadiyah of Makassar. The lecturers always make a good explanation in presenting the materials, namely; prepare before teaching, giving the example from simple to complicated, the lecturers always checking understanding of the students, explaining the material more than one if the material is difficult, and making summarizing of the end in teaching process.